Project quality management : why, what and how - Rose, Kenneth, 1947- (J. Ross Publishing, 2014)
This edition presents case examples that illuminate the theory of quality planning, assurance, and control with real-world narratives, including situation, analysis, and lessons learned. It also provides course discussion points and practical exercises at the end of each chapter. Key features include: Wheel of Quality that codifies in one image the elements of contemporary project quality management; establishes the pillar diagram that provides the needed capability to identify root causes of undesirable effects; supplies quality processes attuned to project scope specifications used to ensure a quality product and quality processes and to help maintain cost and schedule constraints; provides techniques and tools organized and explained according to their application within this process that can be applied to improve project implementation and customer satisfaction in any project context; and examines organization aspects that may hinder quality. -- Edited summary from book.
Keywords: Project management.; Quality control.; elektronické knihy; electronic books